Identification of antibiotic by chromatographic and spectrophotometric methods – A Review - Fatma Anggoro Wahyuningtyas; Alda Safitri Maria Ulfa; Dewi Astri Rahmawati (Asian Journal of Analytical Chemistry, 2023)
The purpose of this article to review the validation and content of antibiotics using various chromatographic and spectrophotometric methods. This review article used five analytical methods on antibiotics, namely high-performance liquid chromatography (HPLC), Fourier transform infrared (FTIR), gas chromatography (GC), ultraviolet-visible (UV-Vis) spectrophotometer and liquid chromatography/mass spectrophotometer (LC/MS) methods. Antibiotics are the most widely used drugs for infections caused by bacteria. Based on a review of several studies related to antibiotic analysis, the general techniques applied are HPLC, FTIR, GC, UV-Vis Spectrophotometry, and LC-MS. Analysis of this antibiotic is a massive challenge due to its sensitivity and instability to various conditions.